Penerapan Pakan Fermentasi Berbasis Limbah Pertanian Lokal terhadap Pertambahan Bobot Badan Kambing Sapera dan Saanen di Tranpol Ujung Batu: Application of Fermented Feed Based on Local Agricultural Waste on Body Weight Gain of Sapera and Saanen Goats at Tranpol Ujung Batu - Saputra, Danang; Yusuf, Dwiky Andryawan; Jiyanto, Jiyanto; Khozin, M.; Auz’i, Ahmad Jovi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Feed availability and quality remain major constraints in smallholder goat farming systems, particularly during the dry season. Agricultural wastes such as cassava peels, corn stalks, cassava leaves, and tofu waste are abundant but underutilized as feed resources. Fermentation technology offers an alternative approach to improve feed quality and palatability. Purpose: This study aimed to evaluate the application of fermented feed based on local agricultural waste on body weight gain of Sapera and Saanen goats at Tranpol Ujung Batu. Methods: The study was conducted for 60 days with a 14-day adaptation period using 70 Sapera and Saanen goats aged 5 months with an average initial body weight of 15 kg/head. Goats were maintained in colony housing systems. Fermented feed consisted of cassava peels and tubers (25%), cassava leaves and stems (20%), corn stalks and cobs (20%), rice bran (15%), tofu waste (15%), molasses (3%), and EM4 (2%). Fermentation was carried out anaerobically for 14 days. Parameters observed included initial body weight, final body weight, total weight gain, and average daily gain (ADG). Data were analyzed descriptively. Results: Fermented feed increased body weight from 15 kg to 20 kg during the maintenance period. Total weight gain reached 5 kg/head with an ADG value of 83.33 g/head/day. Fermented feed also improved feed intake and palatability. Conclusion: Fermented feed based on local agricultural waste has the potential to improve growth performance of Sapera and Saanen goats and may serve as an economical and sustainable feed alternative for smallholder farmers.